Financial development and intergenerational education mobility - Annalisa Russino (Review of Development Finance, 2018)
Using years of education as a measure of status, we study the relationship between financial development and intergenerational mobility, focusing on human capital investments boosted by financial deepening. We consider a set of indices to capture different components of the overall intergenerational education mobility. Using a sample of 39 countries, we find that financial development is related to structural mobility but not to exchange mobility. In particular, while we detect an inverted U-shaped relationship between financial development and structural mobility, we do not find any significant relationship with exchange mobility.
Keywords: 650; Intergenerational mobility; Financial development; Human capital investments; Equality of opportunities